LINUX with operating system concepts - Fox, Richard, 1964- (CRC Press, Taylor & Francis Group, 2015)
Linux with Operating System Concepts merges conceptual operating system (OS) and Unix/Linux topics into one cohesive textbook for undergraduate students. The book can be used for a one- or two-semester course on Linux or Unix. It is complete with review sections, problems, definitions, concepts, and relevant introductory material, such as binary and Boolean logic, OS kernels, and the role of the CPU and memory hierarchy.